2020
DOI: 10.1007/s40544-020-0455-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-mediated tribological characteristics of 40CrNiMoA steel and Inconel 718 alloy during sliding against Si3N4 counterparts

Abstract: A comparative evaluation of the friction and wear behaviors of 40CrNiMoA steel and Inconel 718 alloy sliding against Si3N4 counterparts was conducted over a large temperature range from room temperature (RT) to 800 °C. The temperature-dependent tribological properties associated with the resulting chemical mitigation and structural adaptation of the solid sliding surface were clarified by surface/interface characterizations. The results revealed desirable performance in reducing friction and wear at elevated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Salient findings of some of these studies pertaining to various materials are discussed below. Bai et al [805] studied the tribological characteristics of 40CrNiMoA steel and Inconel 718 alloy during sliding against Si 3 N 4 counterparts in a ball on disc test configuration from room temperature to 800 °C. They reported that the friction coefficients and wear rates of both the alloys decreased at higher temperatures mainly due to the formation of tribo-oxide film.…”
Section: Methodsmentioning
confidence: 99%
“…Salient findings of some of these studies pertaining to various materials are discussed below. Bai et al [805] studied the tribological characteristics of 40CrNiMoA steel and Inconel 718 alloy during sliding against Si 3 N 4 counterparts in a ball on disc test configuration from room temperature to 800 °C. They reported that the friction coefficients and wear rates of both the alloys decreased at higher temperatures mainly due to the formation of tribo-oxide film.…”
Section: Methodsmentioning
confidence: 99%
“…They refer to the layer formed by these oxides as the glaze layer. It has been observed in numerous research that nickel-based alloys can form a glaze layer when subjected to tribological stresses at high temperature [13], [23]. Stott et al explained the formation of such a layer through the compression and compaction of oxidized debris that form at the beginning of the wear process [24].…”
Section: Impact Of the Normal Loadmentioning
confidence: 99%
“…where the friction coefficient is µ, the contact pressure is P, and contact shear stress is τ f . Bai et al [27] conducted experiments to measure the friction coefficient of Inconel 718 at different temperatures. Their results, depicted in Figure 3, were used in the current simulation for accurate analysis.…”
Section: Thermal-mechanical Constitutive Equationsmentioning
confidence: 99%